Proceso atención de enfermería en lactante mayor con gastroenteritis. - Romero Reina, Estefanía Gardenia (2021)
Gastroenteritis is an inflammation of the lining of the lining of the digestive tract that causes nausea, diarrhea, vomiting, and abdominal discomfort. Diarrhea is an intestinal disorder characterized by an increase in the amount or volume of stool, when diarrhea usually lasts for many days, it is usually a sign of a serious problem. The present case study is focused on an older 2-year-old female infant who arrived at the emergency area accompanied by his mother due to a clinical picture of more than 24 hours of evolution characterized by abdominal pain, diarrhea, vomiting in 5 occasions and fever not quantified, after the anamnesis, physical examination and laboratory tests, rotavirus viral gastroenteritis was diagnosed, which is acquired by ingestion of contaminated food and water. It was decided to apply the nursing care process, based on the model of the 11 functional patterns by Marjory Gordon, in which the patterns were identified, after which the taxonomies Nanda (Diagnosis), Nic (interventions) and Noc ( results) with practical theoretical knowledge, which helped with the recovery of the health of the pediatric patient, in addition, an educational talk was given to the mother about the risk factors that lead to suffering from gastroenteritis, adequate hygiene measures such as washing hands after going to the bathroom and before eating, to avoid future relapses.